Controlling Crystal Growth via an Autonomously Longitudinal Scaffold for Planar Perovskite Solar Cells - Duan, Xiaopeng; Li, Xiang; Tan, Licheng; Huang, Zengqi; Yang, Jia; Liu, Gengling; Lin, Zhuojia; Chen, Yiwang (Advanced materials (Weinheim), 2020)
Sequential deposition is certified as an effective technology to obtain high‐performance perovskite solar cells (PVSCs), which can be derivatized into large‐scale industrial production. However, dense lead iodide (PbI2) causes incomplete reaction and unsatisfactory solution utilization of perovskite in planar PVSCs without mesoporous titanium dioxide as a support. Here, a novel autonomously longitudinal scaffold constructed by the interspersion of in situ self‐polymerized methyl methacrylate (sMMA) in PbI2 is introduced to fabricate efficient PVSCs with excellent flexural endurance and environmental adaptability. By this strategy perovskite solution can be confined within an organic scaffold with vertical crystal growth promoted, effectively inhibiting exciton accumulation and recombination at grain boundaries. Additionally, sMMA cross‐linked perovskite network can release mechanical stress and occupy the main channels for ion migration and water/oxygen permeation to significantly improve operational stability, which opens up a new strategy for the commercial development of large‐area PVSCs in flexible electronics. An autonomously longitudinal scaffold constructed by the interspersion of in situ polymerized methyl methacrylate in PbI2 is introduced to effectively eliminate the dependence of sequential deposition on mesoporous TiO2, and is applied in planar perovskite solar cells, with excellent performance. Moreover, this scaffold's cross‐linking grains are capable of releasing mechanical stress, impeding ion migration, and water/oxygen permeation.